2019
DOI: 10.1038/s41586-019-1062-1
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan 1 is a critical mediator of macropinocytosis in pancreatic cancer

Abstract: Summary Pancreatic ductal adenocarcinoma (PDAC) remains recalcitrant to all forms of cancer treatment and carries a dismal 5-year survival rate of 8% 1 . Inhibition of oncogenic KRAS (hereafter KRAS*), the earliest lesion in disease development that is present in >90% of PDAC, and its signaling surrogates has yielded encouraging preclinical results with experimental agents 2 - 4 . However, KRAS*-independent disease recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 30 publications
3
124
1
Order By: Relevance
“…Many factors can be involved in the regulation of the CD138 surface expression, although not in the context of myeloma dissemination. Syntenin and PIP2 have been implicated in controlling endocytic trafficking of CD138 via Arf6-labeled endosomes in epithelial cells [11]. Recycling to the surface was blocked by serum starvation, whereas internalization was not dependent on these adaptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors can be involved in the regulation of the CD138 surface expression, although not in the context of myeloma dissemination. Syntenin and PIP2 have been implicated in controlling endocytic trafficking of CD138 via Arf6-labeled endosomes in epithelial cells [11]. Recycling to the surface was blocked by serum starvation, whereas internalization was not dependent on these adaptors.…”
Section: Discussionmentioning
confidence: 99%
“…Syndecan-1 is a large glycoprotein, carrying heparan sulfate moieties, expressed widely on BM hematopoietic cells, endothelial cells, and on some breast cancer cells. Among its many functions, CD138 has been implicated in wound healing [8], cell adhesion [9], endocytosis [10], and macropinocytosis [11], and may translocate to the nucleus [12]. Hundreds of proteins can bind to CD138, including extracellular matrix components and integrins for adhesion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that macropinocytosis is one mechanism whereby cancer cells scavenge nutrients from the microenvironment to support survival and proliferation (Commisso et al, 2013;Davidson et al, 2017;Hodakoski et al, 2019;Kamphorst et al, 2015;Kim et al, 2018;Lee et al, 2019;Palm, 2019;Palm et al, 2017;Recouvreux and Commisso, 2017;Redelman-Sidi et al, 2018;Yao et al, 2019;Zhang and Commisso, 2019). Due to its large size, fluorescently-labeled dextran is used as a surrogate for macropinocytosis as it cannot be taken up through other endocytic pathways Ivanov, 2008).…”
Section: Inhibition Of Atm Kinase Activity Induces Macropinocytosis Tmentioning
confidence: 99%
“…Macropinocytosis is an endocytic process whereby cells take up fluid, macromolecules, metabolites, and other cargo from the surrounding microenvironment (King and Kay, 2019;Palm, 2019;Zhang and Commisso, 2019). Many studies have evaluated the critical role of macropinocytosis as a nutrient scavenging mechanism in cancers under nutrientdeprived conditions (Commisso et al, 2013;Davidson et al, 2017;Hodakoski et al, 2019;Kamphorst et al, 2015;Kim et al, 2018;Redelman-Sidi et al, 2018;Tejeda-Munoz et al;Yao et al, 2019). To date, these studies have focused on cancers with high PI3K activity, such as those with mutant RAS or PTEN loss, which act upstream of the Rac1-Pak1 actin remodeling pathway to promote macropinosome formation .…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of KRAS-enhanced macropinocytosis represents another possibility to target mutant cancer cells by interfering with their ability to internalize extracellular fluids-containing nutrients. Although the molecular basis of KRAS-driven macropinocytosis is not yet clearly demonstrated, KRAS-dependent expression of Syndecan 1 at the cell surface was recently identified as a molecular mechanism regulating macropinocytosis and indicated as a putative therapeutic target [23]. Moreover, the high internalization of albumin through macropinocytosis can be explored as a drug delivery strategy.…”
Section: Introductionmentioning
confidence: 99%